Pemetaan potensi rawan banjir berdasarkan kondisi fisik lahan secara umum Pulau Jawa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Floods is one of the natural phenomenon which happened in Java Island. Physical land characteristic approach of regional potencies can be used to floods hazard mapping. Parameter which used in floods hazard mapping is landform, mains rock type, soil type, slope area and input by rainfall. Floods are output of natural process which caused by the existence of input (rainfall). Rainfall are especial factor which cause the happening of floods. Usage Of Geographic Information System ( GIS) can be used for overlay by various parameter supporters of cause of floods. Key Words :Floods. Physical characteristic, GIS, Landform, Overlay